2012
DOI: 10.1508/cytologia.77.289
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Droplets of Bacteria, Algae and Fungi and a Relationship between their Contents and Genome Sizes as Revealed by BODIPY and DAPI Staining

Abstract: SummaryWe have developed a convenient method to visualize triacylglycerol-filled lipid droplets (LDs) in some species of bacteria, algae and fungi by staining with borondipyrromethene difluoride (BODIPY). When BODIPY was excited by blue light, LDs emitted green fluorescence, which was distinguished easily from the red autofluorescence of chloroplasts. This makes BODIPY staining suitable for the identification of small amounts of LDs, especially in plants. We first ensured that in Chlamydomonas reinhardtii cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
13
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 29 publications
2
13
0
Order By: Relevance
“…Microscopic analyses of the stained cells showed that LDs form at the edge of the ER, but never at sites between the ER and the chloroplast periphery. The results suggest that in this green alga, LDs form at the ER, like in red algae (Kuroiwa et al 2012). …”
mentioning
confidence: 66%
See 3 more Smart Citations
“…Microscopic analyses of the stained cells showed that LDs form at the edge of the ER, but never at sites between the ER and the chloroplast periphery. The results suggest that in this green alga, LDs form at the ER, like in red algae (Kuroiwa et al 2012). …”
mentioning
confidence: 66%
“…Goodson et al (2011) proposed that LDs in C. reinhardtii are synthesized from both the ER and chloroplasts. In the primitive red alga Cyanidioschyzon merolae, LDs are associated with only the ER (Kuroiwa et al 2012). These results suggest that the formation of LDs is related to both chloroplast growth (in young cells) and chloroplast degradation (in starved cells).…”
mentioning
confidence: 81%
See 2 more Smart Citations
“…LBs can be visualized by microscopy after preferential staining with fluorescent dyes, such as Nile Red or BODIPY, but the latter is thought to be more specific to LBs (Gocze and Freeman, 1994). Some BODIPY dyes also have an advantage over Nile Red in that they can be observed more easily, especially in algae and plants, because their fluorescence color is not masked by red chlorophyll autofluorescence (Kuroiwa et al, 2012). Therefore, we used BODIPY493/503 to visualize LBs in cells during nitrogen depletion (Fig.…”
Section: Lbs and Sgs Visualized In Cells Under Nitrogen-depleted Condmentioning
confidence: 99%